Towards Designing Social Question-and-Answer Systems for Behavioral Support of Individuals with Autism - Hong, Hwajung; Abowd, Gregory; Arriaga, Rosa (EAI Endorsed Transactions on Pervasive Health and Technology, 2015)
Individuals with autism need a network of support to overcome the wide range of challenges in their daily life. Social media hold the promise for improving the quality of life of individuals with autism by offering remote advice for these daily challenges. In the paper, we study an online autism forum as a social question-and-answer (Q&A) venue. We examine 1,277 threads on the forum to characterize topics and types of questions asked by members. Our findings indicate that the majority of questions seek subjective advice and require knowledge about socially appropriate behavior—knowledge perhaps not easily elicited from the forum itself. Based on the identified opportunities and challenges, this paper contributes design recommendations for features in pervasive social computing systems that enhance online Q&A experience for individuals with autism.